A Spontaneous 3D Bone‐On‐a‐Chip for Bone Metastasis Study of Breast Cancer Cells. Issue 12 (5th February 2018) - Hao, Sijie; Ha, Laura; Cheng, Gong; Wan, Yuan; Xia, Yiqiu; Sosnoski, Donna M.; Mastro, Andrea M.; Zheng, Si‐Yang
Abstract: Bone metastasis occurs at ≈70% frequency in metastatic breast cancer. The mechanisms used by tumors to hijack the skeleton, promote bone metastases, and confer therapeutic resistance are poorly understood. This has led to the development of various bone models to investigate the interactions between cancer cells and host bone marrow cells and related physiological changes. However, it is challenging to perform bone studies due to the difficulty in periodic sampling. Herein, a bone‐on‐a‐chip (BC) is reported for spontaneous growth of a 3D, mineralized, collagenous bone tissue. Mature osteoblastic tissue of up to 85 µm thickness containing heavily mineralized collagen fibers naturally formed in 720 h without the aid of differentiation agents. Moreover, co‐culture of metastatic breast cancer cells is examined with osteoblastic tissues. The new bone‐on‐a‐chip design not only increases experimental throughput by miniaturization, but also maximizes the chances of cancer cell interaction with bone matrix of a concentrated surface area and facilitates easy, frequent observation. As a result, unique hallmarks of breast cancer bone colonization, previously confirmed only in vivo, are observed. The spontaneous 3D BC keeps the promise as a physiologically relevant model for the in vitro study of breast cancer bone metastasis. Abstract : A bone‐on‐a‐chip is reported for spontaneous growth of 3D, mineralized, collagenous bone tissue. Mature osteoblastic tissue of up to 85 µm thickness containing heavily mineralized collagen fibers is naturally formed without the aid of differentiation agents. In co‐culture of metastatic breast cancer cells with osteoblastic tissues, unique hallmarks of breast cancer bone colonization, previously confirmed in vivo, are observed.